RIDWAN KAMIL AND TRI RISMAHARINI: LOCAL AND IDEAL LEADERSHIP MODELS IN THE MILLENNIAL ERA - Paramarta, Vip (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
This study discusses the ideal of local leadership models in the millennial era. This research is library research, which collects and analyzes documents, both written documents, pictures and electronics as well as books that discuss leadership, journals and research that have been conducted relating to ideal leadership in millennial generation era. In the millennial era, effective governance will be realized if the leader can meet the qualifications as a credible leader, has the ability, intelligence, and vision far ahead. A good leader must have integrity, honesty, and loyalty for the interests of the people. Millennial leadership needs to support the spirit of independence and entrepreneurship of the millennial generation.